Pemberian Aromaterapi Lavender terhadap Penurunan Nyeri pada Ibu Pasca Sectio Caesarea Study Literature - Elvi Oktavia; Fathia Fakhri Inayati Said; Nurhidayah Amir; Ricky Riyanto Iksan; Roza Indra Yeni (Malahayati Nursing Journal, 2022)
ABSTRACT The prevalence of normal delivery in Indonesia is 86.28%. (IDHS, 2018). Sectio caesarea (SC) surgery is carried out if there are complications, the priority is handling for the safety of the mother and baby. Physically this SC action causes pain in the abdomen. In this case, it is necessary to carry out pain management both pharmacologically and non-pharmacologically. In addition to painkillers, there needs to be a combination method with complementary therapy, namely Lavender Aromatherapy.To determine nursing interventions regarding the administration of lavender aromatherapy and its effect on reducing pain intensity in mothers after sectio caesarea from various journals. The design in this study is a Literature Review. Data Sources Search for research articles in the PubMed (2017-2021), Google Schoolar (2017-2021) and Garuda (2017-2021) databases. The research article search strategy uses the PICOS framework format with keywords: Aromatherapy Lavender "AND" Sectio Caesarea "AND" Pain, "OR" Pain.There are 12 selected articles that can be used in writing literature. That all of the journals used lavender aromatherapy and some used comparisons with other aromatherapy. There is a complementary therapy that is used to help reduce pain in post-SC mothers, namely Lavender Aromatherapy. The technique of administration is very effective by inhalation (inhalation) using candle media, heating furnace, roll on, tissue, cotton and diffuser. Recommendation: Besides being able to reduce the intensity of post-SC pain, it can also overcome anxiety so it is necessary to apply the effect of giving lavender aromatherapy to anxiety in post-SC mothers. Keywords: Lavender Aromatherapy, Pain, Post-Sectio Caesarea         ABSTRAK Prevalensi persalinan normal di Indonesia yaitu sebesar 86,28%. (SDKI, 2018). Tindakan operasi sectio caesarea (SC) dilakukan bila ada komplikasi maka penanganan berprioritas pada keselamatan ibu dan bayi. Secara fisik tindakan SC ini menimbulkan rasa nyeri pada abdomen. Dalam hal ini perlu melakukan manajemen nyeri baik secara farmakologi maupun non-farmakologi. Selain obat-obatan penghilang nyeri perlu ada metode kombinasi dengan terapi komplementer yaitu dengan Aromaterapi Lavender. Mengetahui intervensi keperawatan mengenai pemberian aromaterapi lavender dan pengaruhnya terhadap penurunan intensitas nyeri pada ibu pasca sectio caesarea dari berbagai jurnal. Desain dalam penelitian ini adalah Literature Review. Sumber Data  Pencarian artikel penelitian pada database  PubMed (2017-2021), Google Schoolar (2017-2021) dan Garuda (2017-2021). Strategi pencarian artikel penelitian menggunakan format PICOS framework dengan keyword nya yaitu Aromaterapi Lavender “AND” Sectio Caesarea “AND” Pain, “OR” Nyeri. Terdapat 12 artikel yang terpilih yang dapat digunakan dalam penulisan literature. Bahwa semua dari jurnal tersebut menggunakan aromaterapi lavender dan beberapa menggunakan perbandingan dengan aromaterapi lainnya. Terdapat terapi komplementer yang digunakan dalam membantu menurunkan nyeri pada ibu post-SC yaitu Aromaterapi Lavender. Teknik pemberiannya sangat efektif secara inhalasi (penghirupan) baik menggunakan media lilin, tungku pemanas,roll on, tissue, kapas serta diffuser. Rekomendasi : Selain dapat mengurangi intensitas nyeri pasca SC, dapat juga mengatasi kecemasan sehingga perlu menerapkan pengaruh pemberian aromaterapi lavender terhadap kecemasan pada ibu post SC. Kata Kunci: Aromaterapi Lavender, Nyeri, Post-Sectio Caesarea